(untitled) (Bangladesh Journal of Public Administration, 2023)
The Integrated Land Administration and Management System (ILAMS) is a unified administration of land records, land registration, and land management, which has the potential to align land-related service delivery in a synchronized manner. These three separate service delivery points are required to sync without any mismatching of documents or loss of data. This study has examined the prospect of ILAMS for improving the land administration system of Bangladesh and land-related service delivery. To achieve the objective, relevant secondary data from different sources were used. The land administration of Bangladesh is not efficient, reliable and corruption free, despite the number of initiatives of the government. In addition, records, registration, and management of land are operated through three detached and independent authorities under two different ministries. It creates possibilities of miscoordination and information errors. Registering Property which has been used in Doing Business Ranking is a crucial indicator of economic development and helpful for understanding the business environment of any country. Registering Property consists of six dimensions, which are mutually exclusive and collectively exhaustive. These six dimensions were used for this study to analyze the land administration system of Bangladesh and to explore and establish the prospect of ILAMS. This study however suggests that a single-digitized platform ILAMS can improve land-related delivery in Bangladesh.